Funding Formulae and Strategic Mandate Agreements: The Case of Ontario Universities - Kenno, Staci; Sainty, Barbara (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2025)
This study delves into the evolving landscape of post-secondary education in Ontario between 2012 and 2018, emphasizing accountability and transparency within public universities. Examining the provincial government’s funding formula (FF) and the introduction of strategic mandate agreements (SMAs), the research explores their impact on university strategy. This study investigates the introduction of a new FF, the process of its introduction, and its relation to SMAs. Utilizing semi-structured interviews with university administrators involved in the process, the research employs governmentality and the concept of calculative practices to connect accounting calculations with the governance of the post-secondary education sector. Despite FF adjustments, the study reveals minimal shifts in university behaviour, providing nuanced insights into the complex dynamics of university funding and strategic decision making.